Association between Perceived Stress and Asthma Symptoms in Adolescents - Park, Do Eun; Cho, Seong-Kyung; Cho, Jaelim (Archives of Community Medicine and Public Health, 2016)
Background: Although the effect of psychological stress on asthma has long been suggested, there is little evidence regarding asthma symptoms such as wheezing in relation to perceived stress in adolescents. Objectives: We investigated the relationship between perceived stress and asthma symptoms in a nationally representative sample of Korean adolescents. Methods: We used the data from the eighth Korean Youth Risk Behavior web-based Survey (KYRBS), which is based on a self-reported questionnaire. Perceived stress was classified into five ratings from very high to very low. Asthma symptoms included wheezing and wheezing on exertion during the last 12 months. We performed multiple logistic regression analysis, adjusting for grade (age), sex, asthma history, drinking experience, smoking experience, exposure to secondhand smoke, physical activity, fast food consumption, snack consumption, subjective health status, body mass index category, and household economic status. Results: Of 72,229 participants, 8,224 (11.4%) and 14,658 (20.3%) adolescents reported experiencing wheezing and wheezing on exertion, respectively, during the last 12 months. Participants who reported very high stress had higher odds of wheezing (Odds ratio, 2.621; 95% confidence interval, 2.040–3.367) and wheezing on exertion (1.960; 1.638–2.344) in reference to those with very low stress. With the increase in subjective stress ratings, ORs of wheezing and wheezing on exertion had a rising trend, and the trends were statistically significant (p<0.001 for wheezing and p<0.001 for wheezing on exertion). Conclusions: Perceived stress was positively associated with wheezing and wheezing on exertion in Korean adolescents, both in asthmatics and non-asthmatics.